Strategi Peningkatan Kebutuhan Sistem Jaringan Air Bersih Di Desa Ledu-Ledu, Kecamatan Wasuponda - Yoriyelsa, Yoriyelsa; Arief, Rimba; Azis, Fuad (Fakultas Teknik Universitas Bosowa, 2023)
This study aimed to determine the factors causing the availability of clean water in Ledu-Ledu Village, which is still limited, and what are the strategic directions for increasing the need for a clean water system in Ledu-Ledu Village. The data obtained will then be analyzed using scoring analysis dan SWOT analysis. From the results of the scoring analysis, it can be concluded that 2 (two) factors cause the availability of clean water in Ledu-Ledu Village to be still limited, namely the relatively low rainfall factor of between 2500-3000 mm, and the technological factor which is still lacking in quantity. So the strategy used is the WO strategy which minimizes weaknesses by taking advantage of opportunities